PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOK BERBASIS CANVA UNTUK MENDUKUNG KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK PADA PEMBELAJARAN PPKN KELAS X-1 MAN 1 MUARO JAMBI - Nur Hidayanti; Heri Usmanto; Alif Aditya Candra (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2024)
Background research is based on the importance of the ability to think creatively participants in ppy-study, so it is done. Research is aimed at seeing an increased creative thinking ability in the use of e-book based canva for zero-one class x-1 man 1 muaro jambi. The study USES research and development using the ADDIE model research methods with canva based e-book learning media performed inside the classroom using the smartphone of each protege. Research conducted at man 1 muaro jambi. Research deduced the development of cana-based media learn-based e-book learning met valid, practical, and effective criteria. Valid criteria are validated by experts in materials, media, and language. Results of material validation with an 88% percentage, media validation with a 95% percentage, and language validation with a 70% percentage. Angket practically an educator with a 100% value and protege figure at an 89%. Effective criteria are seen the learner's observation sheets and the test results learn. The results of a 94% learner's observation sheet and the results of the learning results taken were obtained and the scores of each learner increased from the previous test scores. The entire protege also scored above a moderate minimum.